Infección de la orquídea terrestre Phaius tankervilliae (Orchidaceae) con el potexvirus del mosaico del Cymbidium (CymMV) en Costa Rica - Moreira, L. (1999)
In 1996, plants of Phaius tankervilliae cultivated in a nursery in the western region of the Central Valley of Costa Rica, exhibited mild to severe foliar symptoms of chlorotic streak. Flowers from symptomatic plants were similar in size, shape and color to flowers from asymtomatic plants, but the former showed earlier senescence. In some cases, chlorosis and white rings appeared in the sepals. Virus in symptomatic leaf extracts were concentrated by ultracentrifugation and separation in sucrose gradients. Negative staining of partially purified preparations from diseased orchid plants revealed the presence  of filamentous potexvirus-like particles of 500 nm in lenght and 17 nm width. Virus particles contained a single major protein of about 28 kDa as estimated by denaturalizing poli-acrylamide gel electrophoresis (SDS-PAGE) and a single RNA molecule of about 7kb. Infected plants showed a strong specific reaction in double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) using antiserum to cymbidium mosaic virus.